The More Things Change: A Learner's Perspective on Learning Another Arabic Dialect - Elizabeth M. Bergman (Journal of the National Council of Less Commonly Taught Languages, 2010)
This study considers the process of learning another Arabic dialect from a learner’s point of view. It is based on a language learning journal written during the study of Maltese in the summer of 2009. This study considers the context of learning as well as situational and affective factors that aided or impeded it. Its focus, however, is on the learning process itself and on the three steps or stages identified in that process; this is a qualitative rather than quantitative study. Based on these stages, the study proposes questions for further research, experimental and/or empirical, to shed light on the process often described as “easy.” It also makes suggestions for Arabic language instructors and administrators of programs in which Arabic dialects are taught or learned, suggestions to better prepare students to learn an Arabic dialect effectively.